High-frequency repetitive transcranial magnetic stimulation of the left dorsolateral prefrontal cortex may reduce impulsivity in patients with methamphetamine use disorders: A pilot study - Liu, Qingming; Xu, Xingjun; Cui, Huimin; Zhang, Lei; Zhao, Zhiyong; Dong, Da; Shen, Ying (Frontiers in Human Neuroscience, 2022)
Background: Individuals who use methamphetamine (MA) for a long period of time may experience increased impulsivity. In order to reduce impulsivity, high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) has attracted much attention of researchers. Recent work suggests that HF-rTMS over right dorsolateral prefrontal cortex (DLPFC) does not affect the impulsivity of patients with alcohol use disorder; while HF-rTMS over left DLPFC could improve the impulsivity of patients with alcohol use disorder and cigarette smokers. However, it should be noted that empirical studies applying HF-rTMS over left DLPFC of patients with MA use disorders (MAUD) (to evaluate its effect on impulsivity) are still lacking. Methods: A total of 20 sessions of HF-rTMS of the left DLPFC of 29 patients with MAUD were conducted for four consecutive weekdays. At baseline and after the HF-rTMS treatment, the cue-induced craving and stop-signal & NoGo task were assessed. Additionally, 29 healthy controls were recruited. There was no rTMS intervention for the controls, the performance of the stop-signal & NoGo task was evaluated at baseline. Results: In total, 20 sessions of HF-rTMS of the left DLPFC significantly decreased MA-dependent patients’ cue-induced craving and stop-signal reaction time (SSRT). For SSRT, the pretest of experimental group was significantly higher than that of control group, there was no difference between posttest of experimental group and control group. The changes of SSRT were positively correlated with patients’ age in experimental group. Conclusion: Add-on left DLPFC HF-rTMS may be an effective intervention for reducing impulsivity and cue-induced craving of patients with MAUD.